Challenges and facilitating factors in handling domestic medical waste during the COVID-19 pandemic - Syafriani; Sutena, Marthinus; Padmawati, Retna Siwi; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2021)
Objective: To describe the challenges and facilitating factors in handling domestic medical waste during the COVID-19 pandemic based on our community empowerment program in Dusun Ngrombo I, Karangmojo Village, Gunungkidul District, DIY. Content: During the Covid-19 pandemic, medical waste increased in the community, especially for families who were self-isolating at home. In our preliminary study, the community processes waste by burning, burying and throwing it into the environment. Expired medicines are even used as a mixture of plant fertilizers and animal feed. Public literacy about medical waste management is still limited. The local government has not provided medical waste facilities in public spaces. Waste management is not optimal due to the lack of coordination between the relevant government agencies. Furthermore, there has been limited effort from the local primary health care service (puskesmas) to solve medical waste problems. Limited human resources, budgets and different perspectives on regulations cause the puskesmas to resist in responding to these problems. Medical Waste Bank Program is a community waste collection system that manages household medical waste through local waste bank activities. Generally, the Waste Banks (Bank Sampah) in Indonesia only process domestic waste, this program innovates by providing community medical waste services that are needed, especially during this pandemic. Waste bank staff will process the waste that has been collected in the waste bank, then handed over to a third party (private company) through the puskesmas. This can help the puskesmas to reach medical waste in their working areas and also to prevent the transmission of infectious diseases in the community. Conclusion: The waste bank can become a movement to manage community medical waste. Each sector needs to work together in promoting health, providing adequate waste facilities, increasing human resource capacity, as well as monitoring and assisting in managing domestic medical waste.